Pendampingan Pembelajaran Melalui Metode Strorytelling Pada Anak Kelompok B Dalam Rangka Peningkatan Keterampilan Menulis Di RA Miftahul Huda Tlogomojo, Pati - Rahmawati, Laela; Irsyad, Mohammad; Qonaah, Indah; Mahmudah, Umi (IAINU Kebumen, 2023)
This community engagement aimed to enhance the writing skills of Group B children at RA Miftahul Huda Tlogomojo, Pati. The activity involved all students of Group B at RA Miftahul Huda Tlogomojo, Pati. The assistance was conducted in three stages: planning, implementation, and monitoring. The storytelling method was utilized to create an engaging and interactive learning environment. The results showed a significant improvement in the writing skills of the students, as they exhibited enthusiasm and active participation during the sessions. The method fostered creativity and imagination, allowing the children to express their ideas effectively. The support from teachers and staff played a vital role in the success of the program. The community engagement highlights the effectiveness of the storytelling method in promoting writing skills and creating a positive impact on the learning process for young learners at RA Miftahul Huda Tlogomojo, Pati